Stability Analysis of a Multi Area System with Renewable Energy and Multi -Terminal DC Tie Lines - Musau, Moses Peter; Abungu, N.O; Wekesa, Cyrus Wabuge (Journal of Power and Energy Engineering, 2018)
Security constrained multi area multi objective dynamic economic dispatch (SCMAMODED) with renewable energy (RE) and all the possible MTDC stability constraints is formulated for the first time. The stability merits of multi terminal DC (MTDC) tie lines as compared to the traditional HVAC forms the main objective of this paper. Probabilistic load flow (PLF) is applied to determine the system parameters while the uncertainties are modelled using Scenario Based Method (SBM). The simulation results reveal that with the use of MTDC tie lines, the frequency and voltage stability in the MAMODED with renewable energy sources (RES) are enhanced while keeping the MTDC power exchange interface nodes at secure levels
Keywords: Multi -Terminal DC (MTDC) Tie Lines; Probalistic Load Flow (PLF); Renewable Energy Sources (RES); Security Constrained Multi -Area Multi - Objective Economic Dispatch (SCMAMODED); Stability